A Systematic Literature Review on the Role Play Method in Improving Speaking Skills of Elementary School Children - Mukhbita, Alya; Harianja, Chorry Novita; Natania, Mega Lefina; Meywanthi, Nindha Iqlima; Sofyeni, Rezzy Apriska; Pebriana, Putri Hana (The Future of Education Journal, 2025)
The component of language development in children that is uninteresting and less fascinating is what prompted this research to be conducted. In addition, kids frequently struggle when it comes to effectively communicating with their peers, instructors, and the world around them. The approach of role playing is the answer that will allow you to overcome this obstacle. This study will use the approach of role playing to investigate the speaking abilities of primary school pupils in order to determine how well they can communicate. Learning materials may be mastered via the use of the role playing approach, which involves students acting out the roles of inanimate objects and living things. This helps students develop their imaginations and appreciation for the subject matter. The research is conducted using a procedure known as a literature review, which involves looking at a variety of library sources that are pertinent to the subject of the study. According to the findings of the research, the method of role acting has the potential to enhance the acquisition of Indonesian by primary school pupils in terms of their speaking abilities. For the purpose of this study, a literature evaluation of publications published during the past five years was conducted, and a total of fifteen articles that fulfilled the requirements were collected.